2016
DOI: 10.1002/2016gl070409
|View full text |Cite
|
Sign up to set email alerts
|

Low stress drop earthquakes in the rupture zone of the 1992 Nicaragua tsunami earthquake

Abstract: Tsunami earthquakes, events that generate larger than expected tsunami and are deficient in high‐frequency seismic radiation, are rare but hazardous to coastal populations. One model for these events is shallow rupture through low‐strength materials. We calculate seismic moment, corner frequency, and stress drop for 216 earthquakes (2.1 < Mw < 4.7, November 2005 to June 2006) within and external to the 1992 Nicaragua tsunami earthquake rupture zone to test the hypothesis that differences in fault zone properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In this area where only intermediate depth ( z ≃35 km, Figure ) earthquakes are found, low values of Fms and ERM0 are observed. Consistently, in the area of the 1992 rupture, Bilek et al () report low stress drop, and Convers and Newman () report low scaled radiated energy. The seismogenic zone off Nicaragua is, in contrast to the whole Central America segment, almost fully decoupled, as observed with GPS by Correa‐Mora et al ().…”
Section: Differences Among the Subduction Zones And Relations With Sumentioning
confidence: 75%
“…In this area where only intermediate depth ( z ≃35 km, Figure ) earthquakes are found, low values of Fms and ERM0 are observed. Consistently, in the area of the 1992 rupture, Bilek et al () report low stress drop, and Convers and Newman () report low scaled radiated energy. The seismogenic zone off Nicaragua is, in contrast to the whole Central America segment, almost fully decoupled, as observed with GPS by Correa‐Mora et al ().…”
Section: Differences Among the Subduction Zones And Relations With Sumentioning
confidence: 75%
“…Earthquake stress-drop provides direct constraints on earthquake scaling and insights of the hosting fault environments (e.g. Abercrombie 1995; Abercrombie & Rice 2005;Chen & Shearer 2013;Cotton et al 2013;Bilek et al 2016;Thingbaijam et al 2017). Therefore, stress-drop from source spectral fitting techniques has been extensively studied at both regional and global scales (e.g.…”
Section: Discussion Smentioning
confidence: 99%
“…Tsunami earthquakes appear to have very low rupture velocities, such as the 1-1.5 km/s rupture velocity of the 1992 Nicaragua tsunami earthquake (e.g., Kikuchi and Kanamori, 1995;Ihmlé, 1996aIhmlé, , 1996b) and the 1.25-1.5 km/s rupture velocity for the 2010 Mentawai event (e.g., Lay et al, 2011a;Newman et al, 2011). Kanamori et al (2010) and Bilek et al (2011Bilek et al ( , 2016 suggested that other events in the shallow region of tsunami earthquakes may also exhibit low rupture velocities. Variable rupture speeds may exist within an individual earthquake, such as the 2010 Maule (Kiser and Ishii, 2011) event, and rupture velocities may lie along a wide continuum between "typical" and "slow" speeds, such as the ~1.5-2 km/s rupture velocity estimated for the 2013 Santa Cruz Islands earthquake Hayes et al, 2014a).…”
Section: Spectrum Of Slip Velocitiesmentioning
confidence: 99%
“…They found increasing stress drop at 30-60 km depths, and strong along-strike variations that appeared to link areas of high-stress-drop events with zones of little coseismic slip in 2011, south of the region of maximum main-shock slip. Bilek et al (2016) used spectral ratio techniques to compute corner frequencies, seismic moment, and stress drop for a series of earthquakes that occurred within and adjacent to the 1992 Nicaragua tsunami earthquake rupture zone. Earthquakes from 2005 to 2006 that occurred within the 1992 rupture zone exhibited significantly lower corner frequencies and stress drop than those events that occurred adjacent to the 1992 rupture zone, suggesting that regional variations in the megathrust zone that affect rupture processes may persist for many years afterward, if not permanently.…”
Section: Bilek and Lay | Subduction Zone Megathrust Earthquakes Geospmentioning
confidence: 99%